CSR Competition Indicators: How Relative CSR Performance Affects Analyst Recommendations in the Indonesian Market - Kantus , Veronika A. M.; ., Rahmawati; Probohudono , Agung Nur; ., Payamta; Dwianto, Agus (Journal of Ecohumanism, 2024)
How Relative CSR Performance Affects Analyst Recommendations in the Indonesian Market. Our quantitative examination of data from Indonesian firms from 2019 to 2023 explored how analysts assess relative CSR performance and improvements. Screening theory was employed to comprehend how these metrics influence analyst recommendations, considering various contextual aspects. The findings indicate security analysts favor companies with higher or improving CSR performance, though the impact of improvement diminishes over time. Corporations’ relative CSR placements notably affect analysts’ recommendations, with higher positions resulting in more favorable evaluations. The positive consequence of CSR performance enhancements is accentuated for enterprises with higher relative positions and is impacted by factors for instance the number of experts covering the business, the analysts’ experience, and competitive and institutional pressures. This research is restricted to the Indonesian setting, and generalizing the outcomes to other regions or nations with dissimilar CSR practices necessitates further exploration. Additionally, while the concentration is on analysts’ viewpoints, future studies could benefit from inspecting how other stakeholders, for example government agencies or third-party organizations, assess CSR performance. Enterprises in Indonesia ought to center around accomplishing and preserving high relative CSR execution to guarantee positive recommendations from experts. Creating long-haul systems to support CSR performance and understanding the impact of competitive and institutional stresses are pivotal for heightening expert assessments. This investigation adds to the CSR literature by framing CSR competition as a pivotal factor in analysts’ appraisals and broadening screening theory to incorporate unintentional signs. It gives important learning for businesses aiming to skillfully navigate CSR competition and align their procedures with expert desires.